Vegetative development of European pear with quince and different application forms of nutrients Desenvolvimento vegetativo de pereiras europeias com marmeleiros e diferentes formas de aplicação dos nutrientes - Silveira F.N.* (2017)
© 2017, Sociedade Brasileira de Fruticultura. All rights reserved.The pear consumption in Brazil is significant and the country is dependent on the import of this fruit to meet the internal market. The aim of this study was to evaluate the vegetative growth of European pear trees grafted on quince with two application forms of nutrients. The study was conducted during the 2012/2013, 2013/2014 and 2014/2015 harvests, in the experimental area of the Universidade do Estado de Santa Catarina/UDESC, in Lages. The cultivars used were Rocha, Santa Maria and Abbé Fétel. The quinces were ‘Adams’ and ‘EMA’. The application forms of the nutrients were conventional and fertigation. The experiment was carried out in a randomized block design and the arrangement of treatments was sub subdivided plots. The application form of nutrients and rootstocks of quince little influenced on the vegetative growth of the plants, being more influenced by the scion in the soil conditions of this study.